PEMBERDAYAAN SUMBER DAYA MANUSIA DESA MELALUI PEMBUATAN WEBSITE UNTUK PENGEMBANGAN BISNIS DESA - Vegalyra Novantini Samodra; Eko Esti Santoso; Sahar Sahar; Muhamad Sayuti; Lale Ajeng Khalifatun Wardani; Mariana Mariana (Yayasan Nusantara Hasana Berdikari, 2026)
Boosting the village economy requires an approach that is both appropriate and aligned with the community's needs. One effective strategy is leveraging digital technology to promote local potential, disseminate information, and improve the management of village enterprises. This initiative involved creating a website specifically designed to foster economic growth while simultaneously enhancing residents' skills in using and managing digital technology. The project was carried out in several stages, ranging from assessing village needs, designing the website, and discussing business development to providing guidance on system usage. The results demonstrated that the website serves as an effective platform for showcasing the village's products, services, and potential to a wider audience. Furthermore, the initiative helped village officials become more proficient in managing content, updating information, and utilizing technology to support the growth of local businesses. With this website, the village not only gains a modern information platform but also takes a tangible step toward independently strengthening its economy. Ultimately, the success of this endeavor relies heavily on the human resources capable of effectively managing the technology.